2013
DOI: 10.1590/s0100-736x2013001100003
|View full text |Cite
|
Sign up to set email alerts
|

Abundância de Stomoxys calcitrans (Diptera: Muscidae) em diferentes subprodutos canavieiros

Abstract: Um aumento na abundância de Stomoxys calcitrans tem sido observado em áreas de produção sucroalcooleira devido aos subprodutos orgânicos resultantes desta atividade. O objetivo do presente estudo foi avaliar a abundância desta espécie em diferentes subprodutos da cana-de-açúcar. De janeiro a dezembro de 2011, a abundância de S. calcitrans foi monitorada em quatro subprodutos: bagaço, palha, torta de filtro (TF) e palha com vinhaça (PV), em uma usina sucroalcooleira no município de Angélica, Mato Grosso do Sul,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
1
24
1
2
Order By: Relevance
“…Nevertheless, the finding that mixtures at both stages of fermentation were attractive to mated female stable flies suggests that a variety of compounds may be used as oviposition stimulants by stable flies. The mixture of sugarcane straw and vinasse has been shown to correlate with outbreaks of stable flies, particularly during the rainy season, as it increases humidity within the soil and consequently creates a favourable environment for oviposition (Correa et al, 2013). A higher ratio of female stable flies has also been found in sugarcane mills in which vinasse and sugarcane straw have accumulated; this may provide favourable conditions for population growth as a greater number of females enables higher oviposition rates (Correa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the finding that mixtures at both stages of fermentation were attractive to mated female stable flies suggests that a variety of compounds may be used as oviposition stimulants by stable flies. The mixture of sugarcane straw and vinasse has been shown to correlate with outbreaks of stable flies, particularly during the rainy season, as it increases humidity within the soil and consequently creates a favourable environment for oviposition (Correa et al, 2013). A higher ratio of female stable flies has also been found in sugarcane mills in which vinasse and sugarcane straw have accumulated; this may provide favourable conditions for population growth as a greater number of females enables higher oviposition rates (Correa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of vinasse as a fertilizer and the gradual reduction of sugarcane pre-harvest burning resulted in the accumulation of a moist (and nutrient-rich) mulch on the ground, creating large areas of fermenting plant matter, a suitable substrate for the development of immature S. calcitrans (CORRÊA et al, 2013).…”
Section: S Calcitrans Outbreaks In Brazilmentioning
confidence: 99%
“…Using emergence traps to evaluate the potential production of S. calcitrans in distinct organic substrates generated by sugarcane mills, Corrêa et al (2013) found a higher production of stable flies in filter cake and mulch fertigated with vinasse than in sugarcane bagasse and mulch without vinasse. Despite the potentially higher production of S. calcitrans in filter cake than in mulch plus vinasse (55.8 and 24.2 flies/m 2 , respectively), the much larger areas fertigated with vinasse result in a massive production of flies, thus making this substrate the most important one associated with the occurrence of outbreaks.…”
Section: S Calcitrans Outbreaks In Brazilmentioning
confidence: 99%
See 2 more Smart Citations